Electric and dielectric behavior of CaCu3Ti4O12-based thin films obtained by soft chemical method - Ramirez, M. A. [UNESP]; Simões, Alexandre Zirpoli [UNESP]; Felix, A. A. [UNESP]; Tararam, R. [UNESP]; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V. Sa, 2011)
CaCu3Ti4O12 (stoichiometric) and Ca1.1Cu2.9Ti4O12 (non-stoichiometric) thin films have been prepared by the soft chemical method on Pt/Ti/SiO2/Si substrates, and their electrical and dielectric properties have been compared as a function of the annealing temperature. The crystalline structure and the surface morphology of the films were markedly affected by the annealing temperature and excess calcium. The films show frequency-independent dielectric properties at room temperature which is similar to those properties obtained in single-crystal or epitaxial thin films. The room temperature dielectric constant of the 570-nm-thick CCTO thin films annealed at 600 degrees C at 10 kHz was found to be 124. The best non-ohmic behavior (alpha = 12.6) presented by the film with excess calcium annealed at 500 degrees C. Resistive hysteresis on the I-V curves was observed which indicates these films can be used in resistance random access memory (ReRAM). Published by Elsevier B.V.
Keywords: CCTO; Thin films; Electrical properties; Dielectric properties